Studi Tata Ruang Dalam Rumah Adat Kudus - Theresia, Johana (Intra, 2013)
Cultural change it has been going on since the Dutch began to colonize the human and natural resources of indonesia. Depelopment also accurred in the Kudus city, a city district in central java. Villa-style homes are custom homes in the Kudus city that combines the traditional elements of java with european elements. This study discussing what uniqueness that exist in the interior of the sacred customsÂ  terms of arrangement of the room, ornamnets, and the meaning of the decoration by using descriptive method. The results showed thet interior of the house is different from traditional sacred javanese traditional house interior in general, as more carvings that dominate the interior of house and the sculpture has meaning and incorporated elements from outside the island of java, combined with local culture.